Collaborative development: exploring residential design alternatives in Novato, California - Bangerter, Adam Glenn (Kansas State University, 2014)
In Novato, California, zoning regulations and the city’s urban growth boundary (UGB) have restricted development on open agricultural and hillside land outside the city. These restrictions have added to a shortage of affordable homes in Novato in spite of a demand for housing. Population growth estimates suggest that this demand will continue and strategic development of land outside the current city boundaries will need to occur in order over the next 15-20 years (Bay Area Census Data 2010 and Heid 2004). This report outlines a process of land development which evaluates the success of a development alternative relative to what the land owners, developers and the community want, need, and value. This process involved producing four community design alternatives of varying housing densities for an 867 acre parcel of land just beyond Novato’s UGB. The alternatives were: high density (556 homes), medium density (224 homes), low density (14 homes), and low density + land swap (72 homes). Using a systematic scoring process, each alternative was evaluated based on what the land owner, developer, and the community valued in the development and then awarded each a feasibility score. This score represents likelihood of implementation. The higher the feasibility score, the more likely the alternative could be pursued as a development option. The high density alternative (556 homes) received the lowest feasibility score. It met many of the land owner and developer values, but few of the community values. The low density + land swap alternative (58 homes) received the highest feasibility score. This alternative met nearly all of the developer and owner values as well as the community values. The land swap option of this alternative was unique and made this design more feasible. The swap identified land areas on the site property that could be traded for developable land inside the city boundary allowing Novato to maintain the rural character of the city fringe, while giving the developer land that could be used for future development. This alternative is a compromise that adequately addresses the values of all involved and is therefore recommended as the most feasible design possibility.
Keywords: Landscape Architecture; Housing Development; Residential Development; California; Land development; Conservation community design; Area Planning and Development (0341); Landscape Architecture (0390); Land Use Planning (0536)